Rehabilitation of the blind: A review (1992)
Rehabilitation of the blind is an active process whereby the blind person is helped to become an independent and useful member of the community. Rehabilitation thus improves the psychological wellbeing of the blind person as well as making him a happy, contributing member of the society.